The role of the hematological inflammatory index and systemic immuno-inflammation index in acute cholecystitis - Özdemir, Serdar; Altunok, İbrahim; Özkan, Abuzer; İslam, Mehmet Muzaffer; Algın, Abdullah; Eroğlu, Serkan Emre; Aksel, Gökhan (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Acute cholecystitis is one of the most common hepatobiliary emergencies. We aimed to investigate the role of the initial hematological inflammatory index and systemic immuno-inflammation index in predicting short-term mortality in patients with acute cholecystitis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This study with a retrospective observational design was conducted at the emergency department of a tertiary teaching hospital. Patients admitted to our clinic between June 15, 2021, and March 15, 2022, according to the Tokyo criteria were included in the sample. The hematological inflammatory index and systemic immuno-inflammation index were calculated using the hematological test results of the patients evaluated at the emergency department. Survivor and non-survivor groups were formed according to all-cause 30-day mortality. The differences between survivor and non-survivor groups were investigated. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. A total of 194 patients were included in the final analysis. The median age of the study population was 59 (25th–75th percentiles: 46.75–72) years. The rate of all cause-short-term mortality was 7.7. There were significant differences between the survivor and non-survivor groups in terms of the neutrophil count and the systemic immuno-inflammation index (p=0.007, 0.034, respectively; Mann-Whitney U test). No significant difference was found in the remaining laboratory parameters (lymphocyte count, platelet count, and hematological inflammatory index) (p=0.220, 0.489, 0.367 respectively; Mann-Whitney U test). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The systemic immuno-inflammation index was determined to be significantly higher in the non-survivor group than in the survivor group among the patients with acute cholecystitis. However, there was no significant difference between these two groups in relation to the hematological inflammatory index.